Exploring genetic counselors' experiences with non‐paternity in clinical settings. - Cunningham, Emma; Hays, Stephen; Wainstein, Tasha; Zierhut, Heather; Virani, Alice; Tryon, Rebecca (Journal of Genetic Counseling, 2025)
Non‐paternity (NP) is a challenging dilemma faced by genetics providers and there is little consensus on whether this finding should be disclosed. Discussions in the literature are highly theoretical, with limited research regarding how disclosure decisions are enacted in practice. We explored genetic counselors' (GCs) clinical experiences with NP to understand if, how, and why this finding is communicated. Our semi‐structured interviews with genetic counselors in the United States and Canada were analyzed using reflexive thematic analysis to analyze data inductively, describe themes, and present a meaningful interpretation of the data. Eighteen participants who responded to list‐serv messages were interviewed. Our framework describes five salient themes: (1) GC‐lab relationship: the GCs awareness of laboratory processes such as quality control metrics that can uncover NP findings and the way in which a finding of NP was disclosed by the laboratory had an impact on disclosure decisions. This triggered a decision‐making trajectory that involved (2) consultation, (3) ethical reasoning, and (4) practical constraints. GCs frequently consulted other professionals during decision‐making. These conversations impacted disclosure decisions with some consultations carrying greater weight than others. GCs weighed moral concepts of patient autonomy, medical relevance, and preventing harm to rationalize decisions. Access to patients and documentation requirements often dictated how disclosure occurred. Finally, once a decision had been made and enacted, GCs used the experience to reconsider their approach to (5) consenting in future cases, with some GCs altering their pre‐test counseling to always include a discussion of NP. Although NP scenarios are frequently unique in context, our findings demonstrate several common decision‐making factors GCs harness to navigate the identification of NP through clinical genetic testing.